Labor supply, income, and welfare of the farm household - Chang, Yang-Ming; Huang, Biing-Wen; Chen, Yun-Ju (My University, 2012)
Considering family labor and hired labor as heterogeneous inputs, we present a theoretical framework in which the optimal decisions of a farm household on on-farm family and hired labor, off-farm labor supply, and leisure are determined uniquely and endogenously. Focusing on two alternative settings with and without off-farm employment constraints, we show that imperfect substitutability between family labor and hired labor is not critical to the separation of household production and consumption. The validity of the separation proposition is shown to depend crucially on whether or not the availability of off-farm job opportunities is limited. We further examine how changes in external economic conditions and government policies affect the time allocation decisions of the household, as well as the composition of household income (i.e., on-farm income and off-farm labor earnings).
Keywords: Off-farm labor supply; Family and hired labor; Off-farm employment constraints